Advantages and Limitations of Different p62-Based Assays for Estimating Autophagic Activity in Drosophila - Pircs, Karolina (Public Library of Science, 2012)
Levels of the selective autophagy substrate p62 have been established in recent years as a specific readout for basal autophagic activity. Here we compared different experimental approaches for using this assay in Drosophila larvae. Similar to the more commonly used western blots, quantifying p62 dots in immunostained fat body cells of L3 stage larvae detected a strong accumulation of endogenous p62 aggregates in null mutants for Atg genes and S6K. Importantly, genes whose mutation or silencing results in early stage lethality can only be analyzed by microscopy using clonal analysis. The loss of numerous general housekeeping genes show a phenotype in large-scale screens including autophagy, and the p62 assay was potentially suitable for distinguishing bona fide autophagy regulators from silencing of a DNA polymerase subunit or a ribosomal gene that likely has a non-specific effect on autophagy. p62 accumulation upon RNAi silencing of known autophagy regulators was dependent on the duration of the knockdown effect, unlike in the case of starvation-induced autophagy. The endogenous p62 assay was more sensitive than a constitutively overexpressed p62-GFP reporter, which showed self-aggregation and large-scale accumulation even in control cells. We recommend western blots for following the conversion of overexpressed p62-GFP reporters to estimate autophagic activity if sample collection from mutant larvae or adults is possible. In addition, we also showed that overexpressed p62 or Atg8 reporters can strongly influence the phenotypes of each other, potentially giving rise to false or contradicting results. Overexpressed p62 aggregates also incorporated Atg8 reporter molecules that might lead to a wrong conclusion of strongly enhanced autophagy, whereas expression of an Atg8 reporter transgene rescued the inhibitory effect of a dominant-negative Atg4 mutant on basal and starvation-induced autophagy.